Penyelenggaraan Seminar Literasi Digital “Cerdas Membaca, Kreatif Menulis, Bijak Bermedia Sosial” Pada Kegiatan Sasak Literatif 2025 di Desa Bentek, Kab. Lombok Utara - Putra, Sandi Justitia; Mandini, Denda Devi Sarah; Audina, Pin Kharisma; Husbuyanti, Irma El-Mira; Rusyada, Gozin Najah (Puslitbang Sekawan Institute Nusa Tenggara, 2026)
The digital era has changed people's communication patterns, but it has also increased vulnerability to hoaxes, misinformation, and disinformation, especially among groups with low digital literacy levels. This community service activity aims to improve the digital literacy of the people of North Lombok through a Digital Literacy Seminar with the theme